Recorded poor insight as a predictor of service use outcomes: cohort study of patients with first-episode psychosis in a large mental healthcare database - Robert Stewart; Neha Ramu; Anna Kolliakou; Jyoti Sanyal; Rashmi Patel (BMJ Open)
Objectives To investigate recorded poor insight in relation to mental health and service use outcomes in a cohort with first-episode psychosis.Design We developed a natural language processing algorithm to ascertain statements of poor or diminished insight and tested this in a cohort of patients with first-episode psychosis.Setting The clinical record text at the South London and Maudsley National Health Service Trust in the UK was used.Participants We applied the algorithm to characterise a cohort of 2026 patients with first-episode psychosis attending an early intervention service.Primary and secondary outcome measures Recorded poor insight within 1 month of registration was investigated in relation to (1) incidence of psychiatric hospitalisation, (2) odds of legally enforced hospitalisation, (3) number of days spent as a mental health inpatient and (4) number of different antipsychotic agents prescribed; outcomes were measured over varying follow-up periods from 12 months to 60 months, adjusting for a range of sociodemographic and clinical covariates.Results Recorded poor insight, present in 46% of the sample, was positively associated with ages 16-35, bipolar disorder and history of cannabis use and negatively associated with White ethnicity and depression. It was significantly associated with higher levels of all four outcomes over all five follow-up periods.Conclusions Recorded poor insight in people with recent onset psychosis predicted subsequent legally enforced hospitalisations and higher number of hospital admissions, number of unique antipsychotics prescribed and days spent hospitalised. Improving insight might benefit patients’ course of illness as well as reduce mental health service use.